(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Objectives: This study aims to examine the impact of the gas pipeline project proposed between Iran and India in 1989 on the development of their bilateral relations. The objective behind the project was to enhance the economic and strategic ties between the two nations through energy cooperation. Methods: The study adopts a historical and analytical approach by reviewing political and economic negotiations that occurred during the presidencies of Hashemi Rafsanjani (1989–1997) and Mohammad Khatami (1997–2005). It also analyzes secondary sources related to regional dynamics, international pressures, and economic feasibility. Results: Despite continuous discussions and mutual interest, the project failed to materialize. Major obstacles included the high financial cost, political pressure from the United States due to sanctions on Iran’s nuclear program, and security concerns stemming from the India–Pakistan conflict over Kashmir, especially since the proposed pipeline route passed through Pakistani territory. Conclusions: Although the pipeline project was not implemented during the studied period, it represented a strategic attempt to build long-term cooperation between Iran and India. The research highlights the significant role of energy diplomacy and infrastructure in shaping international relations.